Enological tannins affect acetaldehyde evolution, colour stability and tannin reactivity during forced oxidation of red wine. (15th September 2017) - Picariello, Luigi; Gambuti, Angelita; Petracca, Francesca; Rinaldi, Alessandra; Moio, Luigi
Summary: The addition of enological tannins is a practice admitted and widely used to improve wine phenolic compositions. Although wine ageing is an oxidative process involving phenolic compounds and acetaldehyde production and consumption, the effect of enological tannins on the acetaldehyde and chromatic and phenolic changes of a red wine during oxidation is still not known. In this study, three enological tannins preparations containing gallotannins GT, ellagitannins ET and condensed tannins CT were added to a young commercial Lambrusco red wine in order to obtain wines with three different phenolic compositions. Samples were then treated with hydrogen peroxide to trigger oxidation. All added tannins have determined a production of acetaldehyde greater than control. Acetaldehyde was then consumed in 30 days. The samples treated with CT and ET showed, after oxidation, an increase in colour intensity, determined as the sum of 420, 520 and 620 nm absorbances. A simultaneously increase in polymeric pigments was detected. No significant variation of the Saliva Precipitation Index (SPI), an index useful to give an indirect measure of wine astringency, was observed after 30 days of treatment of CT and ET samples. Results highlight that the addition of CT and ET can help to stabilise colour without affecting wine reactivity towards salivary proteins. A significant role of acetaldehyde has been even detected. These are the first data showing the effect of different enological tannins on the production and consumption of acetaldehyde formation during an oxidation process. Abstract : Enological tannins affect the outcome of wine oxidation.